ANALYSIS OF THE AUTHORITY OF THE KPK IN CONTROLLING INVESTIGATIONS, INVESTIGATIONS AND PROSECUTION OF CORRUPTION CRIMINAL ACTS INVOLVING ACTIVE TNI INDIVIDUALS BASED ON ARTICLE 42 OF LAW NUMBER 30 OF 2002 CONCERNING THE CORRUPTION ERADICATION COMMISSION - Ruhiat, Ruhiat; Isnaeni, Belly; Aringga, Rino Dedi (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
This study aims to analyze the authority Commission Corruption Eradication Commission (KPK) in investigations , inquiries and prosecutions criminal acts of corruption involving person The Indonesian National Army (TNI) is active . Focus The main research is based on Article 42 of Law Number 30 of 2002 concerning the Corruption Eradication Committee. This research is motivated by the challenges faced by the Corruption Eradication Committee in handling corruption cases involving active TNI members , considering existence difference jurisdiction between military courts and general courts. This study uses method legal normative approach​ legislation and case studies . The data used in this study are secondary data obtained from legal literature , legislation , documents​ official , and decisions - decisions relevant courts . The analysis was conducted using technique prescriptive to identify legal facts and data systematization based on theoretical framework that has been determined. The results of the study show that the KPK's authority in handling corruption cases involving active TNI personnel Still face various obstacles , especially related to the limitations jurisdiction and authority between the military courts and the Corruption Eradication Committee. Although Thus , Article 42 of Law No. 30 of 2002 provides a legal basis for the Corruption Eradication Committee to carry out investigation , inquiry , and prosecution of these cases . This study also found that the criminal law policy on the authority of the KPK needs to be strengthened so that it can handle corruption cases involving active TNI personnel in a way effective . The KPK has the authority to handle corruption cases involving active TNI personnel , but there needs to be more coordination​ Good between the Corruption Eradication Committee and agencies military to overcome constraint jurisdiction . This study suggests the need to revise the laws that regulate the authority of the Corruption Eradication Committee and the military courts to ensure the effectiveness of handling corruption cases involving active TNI personnel .